Plasmepsin II–III copy number accounts for bimodal piperaquine resistance among Cambodian Plasmodium falciparum - Selina Bopp (Nature Portfolio, 2018)
Piperaquine (PPQ) resistance of Plasmodium is an increasing problem. Here, Bopp et al. find a bimodal dose−response curve of Cambodian isolates exposed to PPQ, with the area under the curve correlating with in vitro PPQ resistance, and show the importance of Plasmepsin II–III copy number to PPQ resistance.